2014
DOI: 10.1007/s10508-014-0425-9
|View full text |Cite
|
Sign up to set email alerts
|

Birth Order and Sibling Sex Ratio in a Population with High Fertility: Are Turkish Male to Female Transsexuals Different?

Abstract: Western studies have consistently found that androphilic (sexually attracted to men) male-to-female transsexuals have a later birth order and a relative excess of brothers compared with appropriate control participants. However, non-Western studies on birth order and sibling sex ratio in androphilic males (transsexual or non-transsexual) are rare. The objective of the study was to test the hypothesis that androphilic male-to-female transsexuals have a late birth order and a relative excess of brothers in a non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…This reaction would become stronger after each pregnancy and could cause both homosexuality and gender dysphoria in assigned males birth. Birth order and sibling ratio have been examined in androphilic transgender women, who were found to be late in birth order and have a predominance of brothers (Blanchard, Zucker, Cohen-Kettenis, Gooren, & Bailey, 1996;Bozkurt, Bozkurt, & Sonmez, 2015;Poasa et al, 2004;Tsoi, Kok, & Long, 1977; VanderLaan & Vasey, 2011). However, a study from South Korea found a predominance of older sisters (Zucker, Blanchard, Kim, Pae, & Lee, 2007).…”
Section: Birth Order Sibling Ratiosmentioning
confidence: 99%
“…This reaction would become stronger after each pregnancy and could cause both homosexuality and gender dysphoria in assigned males birth. Birth order and sibling ratio have been examined in androphilic transgender women, who were found to be late in birth order and have a predominance of brothers (Blanchard, Zucker, Cohen-Kettenis, Gooren, & Bailey, 1996;Bozkurt, Bozkurt, & Sonmez, 2015;Poasa et al, 2004;Tsoi, Kok, & Long, 1977; VanderLaan & Vasey, 2011). However, a study from South Korea found a predominance of older sisters (Zucker, Blanchard, Kim, Pae, & Lee, 2007).…”
Section: Birth Order Sibling Ratiosmentioning
confidence: 99%
“…has also been documented in non-Western cultures including Brazil (VanderLaan et al, 2016), Turkey (Bozkurt, Bozkurt, & Sonmez, 2015), and Samoa Vasey & VanderLaan, 2007).…”
mentioning
confidence: 92%
“…Among cisgender androphilic males, evidence for the FBOE has been found in Canada (Blanchard, 2004; Blanchard & Bogaert, 1996a; Blanchard, Cantor, Bogaert, Breedlove, & Ellis, 2006), China (Li & Wong, 2018), Greece (Apostolou, 2020), Indonesia (Nila, Barthes, Crochet, Suryobroto, & Raymond, 2018; Nila et al., 2019), 1 Italy (Camperio Ciani, Corna, & Capiluppi, 2004), the United Kingdom (King et al., 2005; Kishida & Rahman, 2015; Rahman, Clarke, & Morera, 2009; Xu, Norton, & Rahman, 2019), and the United States (Blanchard & Bogaert, 1996b, 1998; Wampold, 2018; Blanchard & Zucker, 1994; Zucker & Blanchard, 1994). Among transgender or highly femininized androphilic males, evidence for the FBOE has also been found in Brazil (VanderLaan et al., 2016), Canada (Blanchard & Sheridan, 1992; Blanchard, Zucker, Bradley, & Hume, 1995; VanderLaan, Blanchard, Wood, & Zucker, 2014), Samoa (Semenyna, VanderLaan, & Vasey, 2017; VanderLaan & Vasey, 2011; Vasey & VanderLaan, 2007), Iran (Khorashad et al., 2020), the Netherlands (Blanchard, Zucker, Cohen‐Kettenis, Gooren, & Bailey, 1996; Schagen, Delemarre‐van de Waal, Blanchard, & Cohen‐Kettenis, 2012), Spain (Gómez‐Gil et al, 2010), Turkey (Bozkurt, Bozkurt, & Sonmez, 2015), and the United Kingdom (Green, 2000).…”
Section: Introductionmentioning
confidence: 99%